2015
DOI: 10.1007/s13762-015-0813-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing groundwater vulnerability to contamination in an arid environment using DRASTIC and GOD models

Abstract: Groundwater is vulnerable to contamination by anthropological activities. Vulnerability mapping is considered as a fundamental aspect of groundwater management. The aim of this study was to estimate aquifer vulnerability by applying the DRASTIC and GOD models in Abarkooh plain, Yazd province, center of Iran. The DRASTIC model uses seven environmental parameters (depth to water, net recharge, aquifer media, soil media, topography, impact of vadose zone, and hydraulic conductivity) to characterize the hydrogeolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(39 citation statements)
references
References 25 publications
0
33
0
Order By: Relevance
“…Currently, this is the most widely used method for the assessment of aquifer contamination vulnerability. The model is formed by combination of seven hydrogeological parameters, viz D = depth of water table, R = net recharge, A = aquifer media, S = soil media, T = topography, I = impact of vadose zone and C = hydraulic conductivity which are working in coordination to assess the aquifer pollution potential (Al Hallaq and Elaish 2012; Ghazavi and Ebrahimi 2015). In the present study, data of each model parameter have been collected from various sources.…”
Section: Drastic Modellingmentioning
confidence: 99%
“…Currently, this is the most widely used method for the assessment of aquifer contamination vulnerability. The model is formed by combination of seven hydrogeological parameters, viz D = depth of water table, R = net recharge, A = aquifer media, S = soil media, T = topography, I = impact of vadose zone and C = hydraulic conductivity which are working in coordination to assess the aquifer pollution potential (Al Hallaq and Elaish 2012; Ghazavi and Ebrahimi 2015). In the present study, data of each model parameter have been collected from various sources.…”
Section: Drastic Modellingmentioning
confidence: 99%
“…Comparative analysis between DRASTIC results and nitrate levels has been used in several studies (Assaf and Saadeh ; Javadi et al , ; Ghazavi and Ebrahimi ) modified DRASTIC model using nitrate measurements. They showed that correlation coefficient ( R 2 ) between DRASTIC index and nitrate concentration was 0.680 in a modified model, which indicates a good correlation.…”
Section: Resultsmentioning
confidence: 99%
“…Each of these attributes is given a weighing factor reflecting the sensitivity of the system and process to it [15] [16]. These are also given rating factors, based on their values in the specific locations.…”
Section: Techniques and Approachmentioning
confidence: 99%